A Randomized Clinical Trial of a Functional Electrical Stimulation Mimic to Gait Promotes Motor Recovery and Brain Remodeling in Acute Stroke - Xiuyuan Zheng; Danfeng Chen; Tiebin Yan; Dongmei Jin; Zhiqiang Zhuang; Zhimei Tan; Wei Wu (Behavioural Neurology)
Functional electrical stimulation can improve motor function after stroke. The mechanism may involve activity-dependent plasticity and brain remodeling. The aim of our study was to investigate the effectiveness of a patterned electrical stimulation FES mimic to gait in motor recovery among stroke survivors and to investigate possible mechanisms through brain fMRI. Forty-eight subjects were recruited and randomly assigned to a four-channel FES group (n=18), a placebo group (n=15), or a dual-channel FES group (n=15). Stimulation lasted for 30 minutes in each session for 3 weeks. All of the subjects were assessed at baseline and after weeks 1, 2, and 3. The assessments included the Fugl-Meyer Assessment, the Postural Assessment Scale for Stroke Patients, Brunel’s Balance Assessment, the Berg Balance Scale, and the modified Barthel Index. Brain fMRI were acquired before and after the intervention. All of the motor assessment scores significantly increased week by week in all the three groups. The four-channel group showed significantly better improvement than the dual-channel group and placebo groups. fMRI showed that fractional anisotropy was significantly increased in both the four-channel and dual-channel groups compared with the placebo group and fiber bundles had increased significantly on the ipsilateral side, but not on the contralateral side in the group given four-channel stimulation. In conclusion, when four-channel FES induces cycling movement of the lower extremities based on a gait pattern, it may be more effective in promoting motor recovery and induce more plastic changes and brain remodeling than two-channel stimulation. This trial is registered with clinical trial registration unique identifier ChiCTR-TRC-11001615.